2010
DOI: 10.4191/kcers.2010.47.1.075
|View full text |Cite
|
Sign up to set email alerts
|

Thin Film (La0.7Sr0.3)0.95MnO3-δFabricated by Pulsed Laser Deposition and Its Application as a Solid Oxide Fuel Cell Cathode for Low-Temperature Operation

Abstract: The feasibility of using the thin film technology in utilizing lanthanum strontium manganite (LSM) for a solid oxide fuel cell (SOFC) cathode in a low-temperature regime is investigated in this study. Thin film LSM cathodes were fabricated using pulsed laser deposition (PLD) on anode-supported SOFCs with yttria-stabilized zirconia (YSZ) electrolytes. Although cells with a 1 µmthick LSM cathode showed poor low-temperature cell performance compared to that of a cell with a bulk-processed cathode due to the lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…It has been reported that the resistance associated with lateral electronic transport in the cathode is commonly smaller than other resistances from oxygen ion diffusion, and especially smaller than the resistance from the oxygen reduction reaction (ORR). [8][9][10] However, with the improved performance due to the application of nanostructures, the resistance from ion diffusion and ORR are significantly reduced and the proportion of the sheet resistance increases in the total resistance. The sheet resistance of a thin-film cathode is inversely proportional to the thickness of the film; thus, it is possible to reduce the sheet resistance by increasing the thickness of the cathode.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the resistance associated with lateral electronic transport in the cathode is commonly smaller than other resistances from oxygen ion diffusion, and especially smaller than the resistance from the oxygen reduction reaction (ORR). [8][9][10] However, with the improved performance due to the application of nanostructures, the resistance from ion diffusion and ORR are significantly reduced and the proportion of the sheet resistance increases in the total resistance. The sheet resistance of a thin-film cathode is inversely proportional to the thickness of the film; thus, it is possible to reduce the sheet resistance by increasing the thickness of the cathode.…”
Section: Introductionmentioning
confidence: 99%